New Genetically Manipulated Mice Provide Insights Into the Development and Physiological Functions of Invariant Natural Killer T Cells - Ren, Yue; Sekine-Kondo, Etsuko; Tateyama, Midori; Kasetthat, Thitinan; Wongratanacheewin, Surasakadi; Watarai, Hiroshi (Frontiers in Immunology, 2018)
Invariant natural killer T (iNKT) cells are a unique T cell subset that exhibits characteristics of both innate immune cells and T cells. They express V14-J18 (Trav11-Traj18) as an invariant chain of the T cell receptor and are restricted to the MHC class I-like monomorphic antigen presenting molecule CD1d. iNKT cells are known as immune regulators that bridge the innate and acquired immune systems by rapid and massive production of a wide range of cytokines, which could enable them to participate in immune responses during various disease states. Thus, Traj18-deficient mice, Cd1d-deficient mice or iNKT cell-overexpressing mice such as iNKT TCR transgenic mice and iNKT cell cloned mice which contain a V14-J18 rearrangement in the TCR locus are useful experimental models for the analysis of iNKT cells in vivo and in vitro. In this review, we describe the pros and cons of the various available genetically manipulated mice and summarize the insights gained from their study, including the possible roles of iNKT cells in obesity and diabetes.